Analysis of rate spreads for Latin American economies - Battilana, Fiorella; Ruiz, José Luis (Estudios de Administración, 2010)
This study analyzes the determinants of bank spreads to four Latin American countries, focusing on bank-specific factors (liquidity, administrative costs, delinquency, market share, local or foreign institution, merger or acquisition in banks, or if the bank was a new participant); structure of the financial system (market share of foreign banks and concentration); and the macroeconomic environment (inflation, short-term interest rate and GDP growth).